Islamisation in the Indonesian media spaces new sites for a conservative push - Abdullah, Najwa (Journal of religious and political practice, 2018)
The Islamic conservative turn in Southeast Asia has been an important subject of inquiry for many observers of Islam in the region. More recent studies of the conservative turn in the region have noted the differences in the religious orientation, modes of activism, and agendas of the different actors in the country (e.g. work on Front Pembela Islam [FPI], Hizbut Tahrir Indonesia [HTI], Salafis, Traditionalists). This article shows different articulations of Islamisation in Indonesia infiltrating the media after the fall of Soeharto. It seeks to examine new mediums of Islamic propagation promoted by different Islamic actors who use film, radio, and social media, all of which have different social implications in Indonesia's Muslim society. Discussions of media in this article are intertwined with popular culture studies, a field of important scholarly inquiry often overlooked in political and social studies. The development of Islam-based media-in which Islamic pop culture also thrives-is a form of bottom-up Islamisation in Indonesia, which reflects resistance from the various layers of Indonesia's Muslim society towards the Western-led process of globalisation. As apparent in this article, the Islamisation trend in the Indonesian media plays a key role both in pluralising the various discourses of Islam and normalising religious conservatism.